1991
DOI: 10.1148/radiology.180.2.1829843
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial thickness after menopause: effect of hormone replacement.

Abstract: Ultrasound (US) images of the pelvis were evaluated in 112 asymptomatic postmenopausal women to investigate the normal range of endometrial thickness (double-layer measurement) and the effect of hormone replacement on these measurements. Twenty-one patients (19%) had endometrial thickness greater than 0.8 cm. One patient, with an endometrial thickness of 2.5 cm, had endometrial carcinoma. Consideration of the known actions of estrogen and progestogen on the endometrium led the authors to believe that the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(19 citation statements)
references
References 0 publications
1
16
0
2
Order By: Relevance
“…A limit of M-echo thickness at 8 mm [47] or 10 mm [48] was suggested for this category of patients, as the upper limit for normal thickness was also suggested on a value of 9 mm in women receiving treatments associated with thicker endometria (estrogen alone and cyclical combinations) [49-51]. …”
Section: Overviewmentioning
confidence: 99%
“…A limit of M-echo thickness at 8 mm [47] or 10 mm [48] was suggested for this category of patients, as the upper limit for normal thickness was also suggested on a value of 9 mm in women receiving treatments associated with thicker endometria (estrogen alone and cyclical combinations) [49-51]. …”
Section: Overviewmentioning
confidence: 99%
“…The increase in ET is most marked with the use of unopposed oestrogen (57%), followed by use of the sequential oestrogen and progesterone (55%), and is least affected by the continuous combined oestrogen -progesterone regimens (Bonila-Musoles et al, 1995). Some authors recommend a higher ET threshold in women taking HRT (8 mm) (Lin et al, 1991), while one study reported that a cutoff value of 4 mm should be used irrespective of whether or not the patient is taking HRT (Holbert, 1997). If TVUS is used as the initial step in the evaluation of PMB, invasive investigations would be avoided in 40% of women (Dijkhuisen et al, 2000).…”
Section: Transvaginal Ultrasoundmentioning
confidence: 99%
“…Sequential forms of hormone replacement therapy increase endometrial thickness; average measurements are from 5–8.5 mm 50,88–93 . With continuous combined hormone replacement therapy endometrial thicknesses are 4.5–7 mm–still above the mean for atrophic endometrium 50,88–91,93–95 . With tibolone endometrial thickness is less than 5mm 96,97 .…”
Section: Effects Of Hormone Replacement Therapy On the Endometriummentioning
confidence: 99%